Profiling mahua (Bassia latifolia) accessions for flower characters and nutraceutical attributes under north Indian conditions - SINGH, A K; BAJPAI, ANJU; RAVISHANKAR, H; SINGH, V K; SINGH, J P (The Indian Journal of Agricultural Sciences, 2016)
Mahua (Bassia latifolia Roxb.) is a characteristic spontaneous crop species found scattered throughout the tropics and subtropics of the Indian subcontinent. Categorized as an underutilized fruit crop, there is considerable scope to evaluate and characterize the available diverse germplasm in natural stands for promoting its utilization on commercial scale. Keeping the importance of variability in view, 24 accessions collected from different diversity hot spots of the country during 2006-2010 were asexually propagated on seedling rootstocks, planted in the field gene bank and evaluated for flower biology, physicochemical and nutraceutical parameters of the fruit. Approach herkogamy demonstrated by spatial separation of sex organs, existed in the species as an out-crossing mechanism allowing gene flow and genetic introgression in natural stands that contributed to the prevailing diversity. The pollen was 45-55 Î¼m in size, anemophily coexisting with geitonogamy appeared to be the mechanism of pollen transfer. Thus, the flower biology demonstrated floral attributes that accounted for cross pollination resulting in genetic introgression and generation of appreciable diversity in natural stands, emphasizing needs of its characterization for profitable utilization. Based on the attributes, CISH M-4, CISH M-3 and CISH M-8 showed promise in respect of different fruit quality parameters. CISH M-4 outscored others with regard to juice content (65.42 %), pomace (37.94), TSS (26.40 0Brix), Total sugar (23.497 %), Vit C content (64.163 mg/100g) and antioxidant value (44.483 mg AEAC/g). Lack of improved cultivars for commercial utilization, can thus be attended by focused evaluation of mahua germplasm accessions for the fruit quality parameters and their exploitation in further crop improvement programmes.